DETERMINAN AUDIT DELAY DAN PENGARUHNYA TERHADAP REAKSI INVESTOR - Moch Sulthoni (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2012)
Audit delay can be occur in all corporation. Audit delay refers to the length as needed by auditor for company audited from the auditee’s fiscal year-end to the audit report date. On time information will be quick reaction by investor. This reseach divided two model. First model aim to identification and examine what are company size, industry type, financial perfomance, auditor opinion, type of audit firm, and debt ratio. Second model is examine audit delay associated with investor reaction. This reseach use to purposive sampling. Total elected sampling is 486 company 2007-2008. This reseach use to multiple regression. The result first model reseach indicate that from six audit delay variable, three variable influence with audit delay are industry type, financial performance, and type of audit firm. Other variable not influence with audit delay are company size, opinion auditor, and debt ratio. The result second model reseach indicate that audit delay associated with investor reaction proxied by abnormal return and volume trading activity.